Their blood runs cold adventures with reptiles and amphibians - Gibbons, Whit, 1939- (University Alabama Press, 2013)
"Their Blood Runs Cold is entertaining, informative reading that not only enhances our understanding of a unique group of animals, but also provides genuine insight into the mind and character of a research scientist. Whit Gibbons possesses the rare talent of conveying the challenge and excitement of scientific inquiry. A research ecologist who specializes in the study of reptiles and amphibians, he gives accounts of work in the field that are as readable as good short stories. From the dangers of being chased by an angry rattlesnake to the exhilaration of discovering a previously undescribed species, Gibbons brings to life the everyday experiences of the herpetologist as he chases down lizards, turtles, snakes, alligators, salamanders, and frogs in their natural habitats. With essays like 'Turtles May Be Slow but They're 200 Million Years Ahead of Us' and 'How to Catch an Alligator in One Uneasy Lesson,' Their Blood Runs Cold both entertains and informs. The thirtieth anniversary edition of Their Blood Runs Cold features a new prologue and epilogue, additions that address changes in the taxonomy and study of reptiles and amphibians that have occurred since the publication of the original edition and offer suggestions for further reading that highlight the explosion of interest in the topic."--